(untitled) (International Journal of Environmental Sciences, 2025)
Maritime safety is a pressing issue in Indonesia, given the frequent accidents causing substantial human and economic losses. This study examines the disjointed management of marine safety information systems and poor stakeholder coordination as key impediments to effective safety governance. Utilizing a qualitative case study approach, data were gathered via in-depth interviews, field observations, and document analysis. The findings indicate that information systems, scattered across multiple directorates under the Directorate General of Sea Transportation, result in operational inefficiencies and delayed decision-making, policy gaps, including weak inter-agency collaboration and inadequate auditing mechanisms, further compound these challenges. The study proposes an integrated policy network model to enhance collaboration among government bodies, regulatory authorities, and private entities. This framework promotes advanced technology adoption and a robust knowledge-sharing culture to enhance situational awareness and response capabilities, aiming to strengthen Indonesia’s maritime safety framework, reduce accident risks, and enhance overall safety outcomes.